Refractive error and visual acuity of elderly Chinese in Selangor and Johor, Malaysia - Zainora Mohammed; Siti Zawiyah Mansor; Saadah Mohamed Akhir; Bariah Mohd-Ali; Norhani Mohidin (Penerbit Universiti Kebangsaan Malaysia, 2016)
The first aim of this study was to determine the refractive error and visual acuity of Chinese elderly age 60 and above in Selangor and Johor, Malaysia. The second aim was to determine the percentage of elderly with vision impairment. Participants of this study were from the on-going population-based longitudinal study on neuroprotective model for healthy longevity (TUA) among Malaysian older adults using multistage random sampling. A total of 259 Chinese elderly aged 60 and above from state of Selangor and Johor agreed to participate. Refractive error was determined using autorefractometer Retinomax K-plus followed by subjective refraction. Best corrected visual acuity (VA) was measured using logMAR chart. Analysis was performed on data of 202 participants and the remaining 57 were excluded. Overall percentage of refractive error was higher for hyperopia (54%) compared to myopia (23.2%). High percentage of astigmatism was noted for all age groups (> 50%). Both gender showed similar distribution of refractive status. Mean overall VA was 0.24 ± 0.17 logMAR (≅ 6/9–) and mean VA declined with age. Overall, the percentage of elderly having at least mild vision impairment (> 0.3 logMAR or 6/12) was higher (62.9%) compared to normal vision (≤ 0.3 logMAR). However, percentage of vision impairment (VI) was highest in the mild category compared to others and only one participant had severe VI. This study found a high percentage of Chinese elderly with refractive error. The most common type of refractive error was hyperopia. A high proportion of them had mild vision impairment followed by moderate VI even with best correction. Vision impairment could affect daily life functioning and this effect can be further explored in the future.